CO2 electrochemical reduction into CO or C in molten carbonates: a thermodynamic point of view. (1st April 2015) - Chery, D.; Lair, V.; Cassir, M.
Graphical abstract: Highlights: Competing reduction processes in molten alkali carbonates are studied theoretically. The redox systems CO2 /CO, CO2 /C, CO/C, H2 O/H2, Metal + /Metal are investigated. Potential-oxoacidity diagrams are established for binary and ternary eutectics. We focus on different operating conditions for CO2 /CO reduction from 450 to 750 °C. Syngas is theoretically feasible in oxoacidic conditions and relatively high CO pressure. Abstract: This work is a predictive thermodynamic study focused on competing reduction processes in molten carbonates, involving the following redox systems CO2 /CO, CO2 /C, CO/C, H2 O/H2, M + /M (M = Li, Na or K). Its main purpose is to determine the best electrolyte and operating conditions relative to the CO2 reduction into CO or C between 450 and 750 °C, from a theoretical point of view. Potential-oxoacidity diagrams are established at different temperatures for binary eutectics (Li2 CO3 -K2 CO3 : 42.7–57.3 mol.%, Li2 CO3 -K2 CO3 : 62–38 mol.%, Li2 CO3 -Na2 CO3 : 52–48 mol.% and Na2 CO3 -K2 CO3 : 56–44 mol.%), and for the ternary carbonate eutectic Li2 CO3 -Na2 CO3 -K2 CO3 : 43.5–31.5–25 mol.%. As residual water can be present, its reduction into hydrogen is studied as well. The coexistence of CO (g) and H2 (g) in the same phase is theoretically feasible in acidic condition along with a relatively high pressure of CO.